2015
DOI: 10.1002/pssa.201431588
|View full text |Cite
|
Sign up to set email alerts
|

Self‐aligned normally‐off metal–oxide–semiconductor n++GaN/InAlN/GaN high electron mobility transistors

Abstract: Self-aligned normally-off n þþ GaN/InAlN/AlN/GaN MOS HEMTs with a recessed gate show scalable threshold voltage between 1.3 to 3.7 V, which increases with the gate oxide thickness. Al 2 O 3 or HfO 2 gate insulators were grown by ALD at 100 8C so that one photoresist mask could be used for the gate recessing, ALD and metal lift-off. A low density of the barrier surface donors $1 Â 10 13 cm À2 stems from the low thermal budged during the HEMT processing and explains the threshold voltage behaviour. Maximal I DS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…It was reported by several groups that ionized surface donors residing at the III‐N MOS interface can fully compensate the semiconductor surface polarization charge P S , while the density of surface donors ( N d,surf ) can be modified by tailored surface treatment . Particularly we reported that AlGaN/GaN surface pretreatment by HCl prior Al 2 O 3 metal‐organic chemical vapor deposition (MOCVD) followed by post‐deposition annealing (PDA) can lead to fully compensating N d,surf ≈− P S / q , where q is the elementary charge .…”
Section: Introductionmentioning
confidence: 89%
“…It was reported by several groups that ionized surface donors residing at the III‐N MOS interface can fully compensate the semiconductor surface polarization charge P S , while the density of surface donors ( N d,surf ) can be modified by tailored surface treatment . Particularly we reported that AlGaN/GaN surface pretreatment by HCl prior Al 2 O 3 metal‐organic chemical vapor deposition (MOCVD) followed by post‐deposition annealing (PDA) can lead to fully compensating N d,surf ≈− P S / q , where q is the elementary charge .…”
Section: Introductionmentioning
confidence: 89%
“…[7][8][9] In this case, normally-off device operation can be achieved, and, moreover, V th can be increased by oxide thickness (t ox ) increasing to a desired value. 8,10,11 However, polarization charge at the barrier surface is fully compensated in most of the cases by the charge referred here to as surface donors, while its origin and nature has not been understood yet.…”
Section: à2mentioning
confidence: 99%
“…Recently, Al 2 O 3 and HfO 2 grown by ALD at 100 C provided normally-off operation of InAlN/GaN MOS-HEMT with positive V th shift compared to the reference Schottkygated structure and V th increase with the increase in t ox . 11 This has been attributed to the reduction of the surface donors' density from 4.5 to about 1 Â 10 13 cm À2 as a result of low deposition temperature (T D ) during ALD. 11 It has been proposed by several authors that surface donors are located at or close to oxide/III-N barrier interface.…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation
“…2(c) indicate that our device offers a low gate leakage current density of 3 × 10 −8 A=mm at the gate voltage sweep from −3 to +3 V, which is comparable to that of the state-of-the-art Emode planar Al 2 O 3 =GaN ++ =InAlN=AlN=GaN MOS-HEMT but with superior SS performance to the latter. 24 and 2(c) yield a device threshold of V th = 1.2 V, a peak transconductance g m of 38 mS=mm, a field-effect mobility μ FE of ∼250 cm 2 V −1 s −1 , and a drain-induced barrier lowering (DIBL) factor of 110 mV=V. The ON-resistance of the devices is 6 Ω mm, and the estimated breakdown voltage is no less than 20 V. The device I DS and g m values are not higher than those reported previously, 25) owing to (i) the originally lower sheet carrier density at the planar AlGaN=GaN HEMT heterointerface and (ii) the processing-related gate recess depth that intrudes into the AlGaN barrier thickness, which leads to further reduction in the level of 2DEG associated with our inverted-trapezoid fin-FET channel.…”
mentioning
confidence: 99%